2005
DOI: 10.1007/s10886-005-5795-y
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Artemisia annua L. Extract and Artemisinin Activity against Epilachna paenulata and Spodoptera eridania

Abstract: Ethanolic extract of aerial parts of Artemisia annua L. and artemisinin were evaluated as anti-insect products. In a feeding deterrence assay on Epilachna paenulata Germ (Coleoptera: Coccinellidae) larvae, complete feeding rejection was observed at an extract concentration of 1.5 mg/cm2 on pumpkin leaf tissue. The same concentration produced a feeding inhibition of 87% in Spodoptera eridania (Cramer) (Lepidoptera: Noctuidae). In a no-choice assay, both species ate less and gained less weight when fed on leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
1
35
0
3
Order By: Relevance
“…Comparison of our data with those of Maggi et al (2005) indicates that feeding deterrent properties of artemisinin against codling moth neonates are comparable with those against E. paenulata and S. eridania larvae. Maggi et al (2005) needed 0.375 mg of artemisinin per square centimeter (100 mm 2 ) of foliage to obtain deterrence index (calculated as in our study) in the range of 81-87.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Comparison of our data with those of Maggi et al (2005) indicates that feeding deterrent properties of artemisinin against codling moth neonates are comparable with those against E. paenulata and S. eridania larvae. Maggi et al (2005) needed 0.375 mg of artemisinin per square centimeter (100 mm 2 ) of foliage to obtain deterrence index (calculated as in our study) in the range of 81-87.…”
Section: Discussionsupporting
confidence: 60%
“…However, although anticancer and antimalarial activities of A. annua attracted attention of researchers in medical science area (Eastman & Fidock, 2009;Firestone & Sundar, 2009), insect deterrent potentials of this plant and its metabolites are understudied. Maggi et al (2005) showed that both A. annua extracts and synthetic artemisinin reduce pumpkin foliage consumption by larvae of E. paenulata 18.8 *P < 0.05, **P < 0.01, ***P < 0.001 in Fisher's Exact test. and S. eridania.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Utzinger et al, 2001;Xiao et al, 2004), the latter living in the circulatory system of the host. Also, ethanolic extract of aerial parts of A. annua and artemisinin exhibited effect against Epilachna paenulata and Spodoptera eridania (Maggi et al, 2005). A. annua oils are used in the perfume and cosmetic industry (Galambosi, 1980;Jain et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…179 Artemisinin and extracts of the aerial parts of Artemisia annua have been evaluated as anti-insect products. 180 A stereoselective synthesis of (−)-cubebol has been accomplished. 181 Other authors have reported the synthesis of this sesquiterpene and of the hydrocarbon (−)-a-cubebene.…”
Section: This Journal Is © the Royal Society Of Chemistry 2007mentioning
confidence: 99%